Superior Performance in Prone in Infants With Congenital Heart Disease Predicts an Earlier Onset of Walking. (December 2018) - Dagenais, Lynn; Materassi, Manuela; Desnous, Beatrice; Vinay, Marie-Claude; Doussau, Amélie; Sabeh, Pascale; Prud'homme, Joelle; BSc, Karine Gagnon; Lenoir, Marien; Charron, Marc-Antoine; Nuyt, Anne Monique; Poirier, Nancy; et al.
Infants with congenital heart disease are at risk of impaired neurodevelopment, which frequently manifests as motor delay during their first years of life. This delay is multifactorial in origin and environmental factors, such as a limited experience in prone, may play a role. In this study, we evaluated the motor development of a prospective cohort of 71 infants (37 males) with congenital heart disease at 4 months of age using the Alberta Infant Motor Scales (AIMS). We used regression analyses to determine whether the 4-month AIMS scores predict the ability to walk by 18 months. The influence of demographic and clinical variables was also assessed. Fifty-one infants (71.8%) were able to maintain the prone prop position (AIMS score of ≥3 in prone) at 4 months. Of those, 47 (92.2%) were able to walk by 18 months compared to only 12/20 (60%) of those who did not maintain the position. Higher AIMS scores were predictive of a greater likelihood of walking by 18 months ( P < .001), with the scores in prone having a higher predictive ability compared to those in other positions (Exp(B) 15.2 vs 4.0). Shorter hospital stays and female gender were also associated with an earlier onset of walking. In conclusion, our study demonstrates that early ventral performance in infants with congenital heart disease impacts the age of acquisition of walking and could be used to guide referral to rehabilitation.